2005
DOI: 10.1261/rna.5040605
|View full text |Cite
|
Sign up to set email alerts
|

The bipartite structure of the tRNA m1A58 methyltransferase from S. cerevisiae is conserved in humans

Abstract: Among all types of RNA, tRNA is unique given that it possesses the largest assortment and abundance of modified nucleosides. The methylation at N 1 of adenosine 58 is a conserved modification, occurring in bacterial, archaeal, and eukaryotic tRNAs. In the yeast Saccharomyces cerevisiae, the tRNA 1-methyladenosine 58 (m 1 A58) methyltransferase (Mtase) is a two-subunit enzyme encoded by the essential genes TRM6 (GCD10) and TRM61 (GCD14). While the significance of many tRNA modifications is poorly understood, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 44 publications
(55 reference statements)
2
114
0
1
Order By: Relevance
“…To examine the consequence of m 1 A58 hypomodification and further establish our array method as a suitable tool for functional studies, we performed siRNA experiments on either of the human m 1 A58 methyltransferase subunits, TRM6 or TRM61 (Ozanick et al 2005). We chose to carry out this experiment with MDA-MB-231 cells because tRNAs are known to be overexpressed in these cells (Pavon-Eternod et al 2009), and this high amount of tRNA may be more sensitive to variations in this modification enzyme.…”
Section: Sirna Knockdown Of M 1 A58 Methyltransferase Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the consequence of m 1 A58 hypomodification and further establish our array method as a suitable tool for functional studies, we performed siRNA experiments on either of the human m 1 A58 methyltransferase subunits, TRM6 or TRM61 (Ozanick et al 2005). We chose to carry out this experiment with MDA-MB-231 cells because tRNAs are known to be overexpressed in these cells (Pavon-Eternod et al 2009), and this high amount of tRNA may be more sensitive to variations in this modification enzyme.…”
Section: Sirna Knockdown Of M 1 A58 Methyltransferase Subunitsmentioning
confidence: 99%
“…Among the over 30 tRNAs sequenced, only two, rat tRNA Asp and tRNA Glu , have been reported to be unmodified at position 58 (Kuchino et al 1981;Chan et al 1982). The human homolog of the yeast tRNA m 1 A methyltransferase has been identified and it has been shown to have the same two subunit composition as the methyltransferase from yeast (Ozanick et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The situation in human is strikingly similar, and the human homologs TRMT6 and TRMT61A show 20% and 30% similarity to the yeast enzymes at the amino acid level, respectively. 17,54 Supporting this conserved role, ALKBH1 was recently reported to demethylate m 1 A58 in human tRNA iMet as well as several other tRNA species. 55 Loss of ALKBH1 increases the cellular tRNA iMet level, corroborating the idea that m 1 A58 methylation is essential for tRNA iMet stability.…”
Section: Trnamentioning
confidence: 85%
“…16 However, numerous other modifications have been added to the mRNA repertoire. m 1 A has been described in tRNA and rRNA, 17,18 but we now know that it is also present in mRNA, albeit at levels approximately 10-fold lower than m 6 A. 19,20 In the studies that first described its distribution in mRNA, one identified 7,154 peaks in 4,151 coding genes, 19 while the other identified 887 peaks in 600 genes.…”
Section: Mrnamentioning
confidence: 99%
“…The tRNA T-loop at position 58 commonly contains a m 1 A modiication [50], along with position 9 of metazoan mitochondrial tRNAs [51] and eukaryotic rRNAs [52]. Initiator tRNA C marks stabilize the secondary structure of tRNA, alter aminoacylation and codon recognition [56], and regulate translational idelity [57].…”
mentioning
confidence: 99%